Hey u are in which school.Same to same wuestions .!

Questions*

u r in which school??

Hmm...Tell in inbox... I am also telling there...

Log in to add a comment

Hey u are in which school.Same to same wuestions .!

Questions*

u r in which school??

Hmm...Tell in inbox... I am also telling there...

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

2(0.3)³ + (0.4)³ + (0.5)³ + (-0.7)³ + (-0.8)³

=*(0.3)³ + (0.3)³* + (0.4)³ + (0.5)³ + (-0.7)³ + (-0.8)³

= (0.3)³ + (0.4)³ + (-0.7)³ + (0.3)³ + (0.5)³ + (-0.8)³

=**[**(0.3)³ + (0.4)³ + (-0.7)³**]** + **[**(0.3)³ + (0.5)³ + (-0.8)³**] ------------------(1)**

We know that **if a+b+c=0, then a³+b³+c³ = 3abc**

In**[**(0.3)³ + (0.4)³ + (-0.7)³**]; **

0.3 + 0.4 + (-0.7) = 0.7 -0.7 = 0

So (0.3)³ + (0.4)³ + (-0.7)³

= 3×0.3×0.4×(-0.7)

⇒**[**(0.3)³ + (0.4)³ + (-0.7)³**] **= -0.252 ------------------------------------(2)

Similarly In**[**(0.3)³ + (0.5)³ + (-0.8)³**]; **

0.3 + 0.5 + (-0.8) = 0.8 -0.8 = 0

So (0.3)³ + (0.4)³ + (-0.7)³

= 3×0.3×0.5×(-0.8)

⇒**[**(0.3)³ + (0.5)³ + (-0.8)³**] **= -0.360 ------------------------------------(3)

So putting equation (2) and (3) in equation (1)

**[**(0.3)³ + (0.4)³ + (-0.7)³**]** + **[**(0.3)³ + (0.5)³ + (-0.8)³**] **

= (-0.252) + (-0.360)

=**-0.612**

So 2(0.3)³ + (0.4)³ + (0.5)³ + (-0.7)³ + (-0.8)³ = -0.612

=

= (0.3)³ + (0.4)³ + (-0.7)³ + (0.3)³ + (0.5)³ + (-0.8)³

=

In

0.3 + 0.4 + (-0.7) = 0.7 -0.7 = 0

So (0.3)³ + (0.4)³ + (-0.7)³

= 3×0.3×0.4×(-0.7)

⇒

Similarly In

0.3 + 0.5 + (-0.8) = 0.8 -0.8 = 0

So (0.3)³ + (0.4)³ + (-0.7)³

= 3×0.3×0.5×(-0.8)

⇒

So putting equation (2) and (3) in equation (1)

=

So 2(0.3)³ + (0.4)³ + (0.5)³ + (-0.7)³ + (-0.8)³ = -0.612

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

we use the Algebra formula : **a³ + b³ + c³ = 3 a b c if a+b+c =0**

we observe that 0.3 + 0.4 + (-0.7) = 0

and , 0.3 + 0.5 + (-0.8) = 0

LHS = 0.3³ + 0.4³ + (-0.7)³ + 0.3³ + 0.5³ + (-0.8)³

= 3 * 0.3 * 0.4 * (0.7) + 3 * 0.3 * 0.5 * (-0.8)

= - 0.9 * (0.28 + 0.40)

* = - 0.612*

we observe that 0.3 + 0.4 + (-0.7) = 0

and , 0.3 + 0.5 + (-0.8) = 0

LHS = 0.3³ + 0.4³ + (-0.7)³ + 0.3³ + 0.5³ + (-0.8)³

= 3 * 0.3 * 0.4 * (0.7) + 3 * 0.3 * 0.5 * (-0.8)

= - 0.9 * (0.28 + 0.40)